(Fatal) Woman, Carnality and Death: Iconographic Treatment of the Female Corpse in The Autopsy of Jane Doe (2016) - Clemente Fernández, M.ª Dolores (Eikón / Imago, 2023)
This text addresses the artistic theme of women as the embodiment of death through the motif of the female corpse in the film The Autopsy of Jane Doe (André Øvredal, 2016). The construction of the character of the dead woman is based on the stereotype of the fatal woman, connecting with misogynistic iconographies that demonize female sexuality through the link between evil and carnality. In the iconographic analysis, cultural products are critically analyzed from a feminist approach that find their reason for being in a gendered condition of evil, becoming aware of the ideology that permeates them. Beauty is conceived as a trap or artifice, relating the female body with temptation, danger, death and corruption. Under the cover of a fantastic narrative, old moralistic clichés are updated that rest on aesthetic definitions of beauty/ugliness loaded with patriarchal implications.